Sosialisasi Modul Ajar Berbasis Digital Bagi Guru MTs. Swasta Ummul Quraa - Wahyuni, Ratna; Nasution, Haryati Ahda; Siregar, Alwi Gery Agustan (Universitas Negeri Gorontalo, 2025)
The Merdeka Curriculum is an innovative step in the Indonesian education system which aims to improve the quality of learning based on student needs and potential. This service aims to develop teaching modules that are in accordance with the principles of the Independent Curriculum, namely learning that is student-centered, flexible, and relevant to the needs of the 21st century for Ummul Quraa Private MTs teachers. Socialization Teaching modules are designed to provide contextual learning experiences, oriented towards developing students' literacy, numeracy and character competencies. These benefits include improving the quality of learning, optimizing the use of school resources, and strengthening collaboration between teachers, students